2019
DOI: 10.21873/invivo.11524
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ARID1A in Endometrial Cancer and the Molecular Pathways Associated With Pathogenesis and Cancer Progression

Abstract: AT-rich interaction domain 1A gene (ARID1A) encodes for a subunit of the switch/sucrose non-fermentable (SWI/SNF) complex, a chromatin remodeling complex, and it has been implicated in the pathogenesis of various cancer types. In this review, we discuss how ARID1A is linked to endometrial cancer and what molecular pathways are affected by mutation or inhibition of ARID1A. We also discuss the potential use of ARID1A not only as a prognostic biomarker, but also as a target for therapeutic interventions. The dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 77 publications
(80 reference statements)
0
22
0
Order By: Relevance
“…Furthermore, the process of epithelial-to-mesenchymal transition (EMT) seems to be crucial in the development of adenomyosis but also plays an important role in carcinogenesis [ 31 , 32 ]. Several studies have shown that changes in genes like AT-rich interactive domain-containing protein 1A (ARID1A), PTEN, KRAS, phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha (PIK3CA) and Serine/threonine-protein phosphatase 2A 65 kDa regulatory subunit A alpha isoform (PPP2R1A) are present in women with endometriosis, but these are also known cancer-driving mutations involved in endometrial cancer carcinogenesis [ 33 , 34 ]. However, cancer-associated mutations were also found in endometriotic lesions without concurrent cancer, in particular in deep infiltrating lesions which are rarely associated with cancer development [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the process of epithelial-to-mesenchymal transition (EMT) seems to be crucial in the development of adenomyosis but also plays an important role in carcinogenesis [ 31 , 32 ]. Several studies have shown that changes in genes like AT-rich interactive domain-containing protein 1A (ARID1A), PTEN, KRAS, phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha (PIK3CA) and Serine/threonine-protein phosphatase 2A 65 kDa regulatory subunit A alpha isoform (PPP2R1A) are present in women with endometriosis, but these are also known cancer-driving mutations involved in endometrial cancer carcinogenesis [ 33 , 34 ]. However, cancer-associated mutations were also found in endometriotic lesions without concurrent cancer, in particular in deep infiltrating lesions which are rarely associated with cancer development [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the mutant spectra of EOVC and EC (Table 2), many shared mutant genes have been identified: ARID1A, TP53, PTEN, PIK3CA, KRAS, CTNNB1, MMR, POLE, among others (51). However, the frequency of mutation of these genes appears to vary depending on different microenvironmental effects (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Synchronous Ovarian and Endometrial Carcinomamentioning
confidence: 99%
“…Summary of most common molecular alterations in EOVC and EEC(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60).…”
mentioning
confidence: 99%
“…We had almost no HER2 overexpression, so no correlations with the prognosis could be established [29]. Loss of ARID1A has been linked to shorter progression-free survival in EC, and loss of PTEN might be a good prognostic factor [30,31]. Our results are similar in terms of the positive proportion of cases for both biomarkers, but we did not nd any statistical signi cance related to survival.…”
Section: Discussionmentioning
confidence: 53%